A Hybrid of DL and WYL Nonlinear Conjugate Gradient Methods. (25th March 2014) - Yao, Shengwei; Qin, Bin
Abstract : The conjugate gradient method is an efficient method for solving large-scale nonlinear optimization problems. In this paper, we propose a nonlinear conjugate gradient method which can be considered as a hybrid of DL and WYL conjugate gradient methods. The given method possesses the sufficient descent condition under the Wolfe-Powell line search and is globally convergent for general functions. Our numerical results show that the proposed method is very robust and efficient for the test problems.